Modeling Cerebral Blood Flow Dependence on Carbon Dioxide and Mean Arterial Blood Pressure in the Immature Brain With Accounting for the Germinal Matrix - Sidorenko, Irina; Turova, Varvara; Botkin, Nikolai; Eckardt, Laura; Alves-Pinto, Ana; Felderhoff-Müser, Ursula; Rieger-Fackeldey, Esther; Kovtanyuk, Andrey; Lampe, Renée (Frontiers in Neurology, 2018)
Intracerebral hemorrhage (ICH) is one of the most critical complications in the development of preterm infants. The likelihood of ICH is strongly associated with disturbances in cerebral blood flow (CBF) and with microvascular fragility in the germinal matrix (GM). The CBF value and its reactivity to changes in arterial carbon dioxide pressure (pCO2) and mean arterial pressure (MAP) are relevant indicators in the clinical assessment of preterm infants. The objective of the present study is mathematical modeling of the influence of pCO2 and MAP on CBF in immature brain, based on clinical data collected from 265 preterm infants with 23-30 gestational weeks. The model was adapted to the peculiarities of immature brain by taking into account the morphological characteristics of the GM capillary network and vascular reactivity, according to gestational and postnatal age. An analysis of numerically calculated values of CBF and its reactivity to changes in MAP and pCO2 was performed separately for each gestational week and for the first two days of life both for preterm infants with and without ICH. The developed model for the estimation of CBF was validated against equivalent experimental measurements taken from the literature. A good agreement between estimated values of CBF and the equivalent numerical and experimental values confirms the potential use of the model in the analysis of hazardous combinations of MAP and pCO2 that expose the microvasculature of GM to damage.